2017
DOI: 10.1038/srep45021
|View full text |Cite
|
Sign up to set email alerts
|

Neutron scattering observation of quasi-free rotations of water confined in carbon nanotubes

Abstract: The translational and orientational dynamics of water in carbon nanotubes has been studied by quasi-elastic neutron scattering from 300 down to 10 K. Results show that, reducing temperature below 200 K, part of this water behaves as a quasi-free rotor, that is, the orientational energy of such molecules becomes comparable to the rotational energy of water in the gas phase. This novel and unique dynamic behavior is related to the appearance of water molecules characterized by a coordination number of about two,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…1, the isotropic spread of incoherent scattering over a 4p solid angle, 18 and quasi-elastic neutron scattering (QENS) results on this same system reported elsewhere. 9…”
Section: Nse Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…1, the isotropic spread of incoherent scattering over a 4p solid angle, 18 and quasi-elastic neutron scattering (QENS) results on this same system reported elsewhere. 9…”
Section: Nse Experimentsmentioning
confidence: 99%
“…In particular, confinement of water in nanometric cavities -especially in cylindrical nanopores -represents a topic of general interest, since low-dimensional water is a prototypical non-bulk system that is widespread in nature [1][2][3] and synthetic structures of technological importance. 4,5 In this context, carbon nanotubes (CNTs), which are peculiar allotropes of carbon characterized in terms of diameter and (n,m) chiral indices, 6 have become popular in the field of nanofluidics as effective geometries to study small-molecule polar liquids under quasi-1D ultra-hydrophobic confinement, [7][8][9] especially in their single-wall carbon nanotube (SWCNT) declination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it has recently been reported that water, when confined in beryl crystal, exhibits ferroelectric properties 28 because an intermolecular distance of 5 Å is sufficient to alleviate the tetrahedral orientation from bulk water hydrogen bonding. A similar situation arises when water is confined inside a carbon nanotube 29 , 30 . We note that the average spacing between water molecules in our pp-matrix is of similar magnitude, which could allow a ferroelectric phase of water to exist.…”
Section: Resultsmentioning
confidence: 83%
“…Meanwhile, between CNFs, spatial confinement is also formed. Numbers of work has shown that water in confined space show distinct behaviour compared to bulk water [27][28][29][30] . At micron scale, the capillary force on the water in the different CNF superstructure should be taken in account, just as the cell structure and lumen of wood cell.…”
mentioning
confidence: 99%